Intermittent feeding of Chlortetracycline to finishing cattle - Riley, Jack G.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station, 2011)
We used 168 yearling steers in a 139-day finishing trial to evaluate high levels of chlortetracycline (aureomycin) fed for short periods at regular intervals during finishing. Since liver abscess rate was low for all treatments including the nonmedicated controls and health status was good, chlortetracycline (CTC) did not significantly affect abscess rate or feedlot performance.
Keywords: Beef; Chlortetracycline; Finishing cattle; Abscess rate